The Gambia : Request for Disbursement Under the Rapid Credit Facility, and Proposal for a Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses The Gambia's Request for Disbursement Under the Rapid Credit Facility, and Proposal for a Staff-Monitored Program. The authorities have committed to lowering net domestic borrowing (NDB) from 11.4 percent in 2016 to a fiscal anchor of 1 percent of GDP in 2017 and beyond, and refraining from monetary financing. External budget support of 7.2 percent of GDP will be complemented by a set of non-tax revenue and expenditure measures of 5 percent of GDP to achieve the NDB target. The IMF staff supports the authorities' request. The IMF staff also views the package of measures the authorities have committed to as representing a very significant adjustment effort.